A review of ammonia-oxidizing bacteria and archaea in Chinese soils - He, Ji-Zheng; Shen, Ju-Pei; Zhang, Li-Mei; Di, Hong J (Frontiers in Microbiology, 2012)
Ammonia (NH3) oxidation, the first and rate-limiting step of nitrification, is a key step in the global Nitrogen (N) cycle. Major advances have been made in recent years in our knowledge and understanding of the microbial communities involved ammonia oxidation in a wide range of habitats, including Chinese agricultural soils. In this mini-review, we focus our attention on the distribution and community diversity of ammonia-oxidizing bacteria (AOB) and ammonia oxidizing archaea (AOA) in Chinese soils with variable soil properties and soil management practices. The niche differentiation of AOB and AOA in contrasting soils have been functionally demonstrated using DNA-SIP (stable isotope probing) methods, which have shown that AOA dominate nitrification processes in acidic soils, while AOB dominated in neutral, alkaline and N-rich soils. Finally, we discuss the composition and activity of ammonia oxidizer in paddy soils, as well as the mitigation of the greenhouse gas nitrous oxide (N2O) emissions and nitrate leaching via inhibition of nitrification by both AOB and AOA.